2017
DOI: 10.1111/vox.12488
|View full text |Cite
|
Sign up to set email alerts
|

Diverse and novel RHD variants in Australian blood donors with a weak D phenotype: implication for transfusion management

Abstract: The array of RHD variants detected in this study indicated diversity in the Australian donor population that needs to be accommodated for in future genotyping strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…The c.939+3A>C substitution also showed a major exclusion of exon 6 from the mature transcript. RHD (c.635‐2A>C) and RHD (c.939+3A>C) have been suspected to be partial D alleles, suggesting that at least one D epitope is altered, possibly by insertion/deletion (indel) of amino acid(s) in these specific cases. Although we have clearly shown that they are both SS variants, there is no molecular evidence for short inframe (nucleotide) indels in our model, indicating that the molecular mechanism underlying the putative partial D phenotype associated with these variants remains to be characterized by additional studies, ideally with fresh blood samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The c.939+3A>C substitution also showed a major exclusion of exon 6 from the mature transcript. RHD (c.635‐2A>C) and RHD (c.939+3A>C) have been suspected to be partial D alleles, suggesting that at least one D epitope is altered, possibly by insertion/deletion (indel) of amino acid(s) in these specific cases. Although we have clearly shown that they are both SS variants, there is no molecular evidence for short inframe (nucleotide) indels in our model, indicating that the molecular mechanism underlying the putative partial D phenotype associated with these variants remains to be characterized by additional studies, ideally with fresh blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…An up‐to‐date review of the literature and the RhesusBase was performed . On the basis of their position relative to the constitutive SSs, 15 variations of the RHD gene, including eight exonic (i.e., first, antepenultimate and penultimate position of exons) and seven intronic variants were selected for functional analysis (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…However, advanced molecular typing platforms such as SNP‐microarray and DNA sequencing, including massively parallel sequencing, have now become increasingly available in reference typing laboratories to detect and genetically classify RHD variants . For clinicians, early identification of individuals with partial D would help guide patient management in the obstetric population …”
Section: Discussionmentioning
confidence: 99%
“…Rh phenotyping was performed following accredited standard agglutination test tube method using anti‐D, anti‐C, anti‐c, anti‐E, and anti‐e monoclonal antibodies (MoAbs; Epiclone, CSL) phenotyping reagents. RhD epitope mapping was performed using a RhD typing kit (ALBAclone Advanced Partial RhD typing kit, Alba Bioscience Ltd.) according to the manufacturer's instructions …”
Section: Methodsmentioning
confidence: 99%
“…The D‐epitope profile was performed using anti‐D MoAbs (ALBAClone, Alba Bioscience Ltd) by indirect antiglobulin test (IAT) and adsorption and elution technique with untreated and papain‐treated reagent RBCs (Phenocell A, bioCSL) . The anti‐D MoAbs (ALBAClone) were different from the aforementioned Australian DEL prevalence study .…”
Section: Methodsmentioning
confidence: 99%